The Weight of Patriarchy? Gender Obesity Gaps in the Middle East and North Africa (MENA) - Joan Costa-Font; Mario Gyori (Institute of Labor Economics (IZA), 2020)
The worldwide obesity epidemic has impacted women more heavily than men. These gender-based differences are particularly pronounced in the Middle East and North Africa (MENA) region where gender obesity gaps on average exceed 10 percentage points. This paper examines one of the explanations, namely the role of female empowerment on gender gaps in obesity. We study the effect of several measures of female empowerment including female labour market participation on gender obesity gaps over a time span of 41 years (1975-2016) in a sample of 190 countries. We document that after controlling for a number of relevant controls, gender obesity gaps are only associated to measures of female empowerment in the MENA region but that this is not true worldwide. We then use an instrumental variable approach in order to illustrate that the causality runs indeed from empowerment, proxy it by both labour market and political participation to gender obesity gaps and not vice versa. Our results reveal that a one percentage point increase in female labor market participation (female MPs in national parliament) predicts a 0.2 (0.09) percentage point decrease in gender gaps in obesity in the MENA region.
Keywords: I18; J16; 330; Middle East and North Africa Region; female political participation; female labour market participation; female empowerment; obesity; female overweight